Design, implementation and analysis of full coupled monitoring system of FPSO with soft yoke mooring system. (1st February 2016) - Wu, Wenhua; Wang, Yanlin; Tang, Da; Yue, Qianjin; Du, Yu; Fan, Zheliang; Lin, Yang; Zhang, Yantao
Abstract: Due to the complexity of the marine environment loading and motions of vessels, many uncertainties are involved in the design of mooring systems. This paper designs a fully monitoring system, including meteorological–environmental and mechanical aspects. The environmental monitoring system is composed of current, wave and wind equipments. Fiber Bragg Gauges/FBG, incline sensors and GPS/INS form the mechanical monitoring system. On the basis of dynamic characteristic of the soft yoke system, a restore force measurement method has been proposed according to the response of the angular information of the soft yoke. The monitoring system has been installed on one FPSO in Bohai Bay, and comprehensive monitoring information has been obtained from 2011. The calculation of the restoration force of the mooring system by the present dynamic method shows high agreements with that of the FBG. The vessel motions in the frequency domain calculated by the measured wave spectrum multiplied by the designed RAO (Response Amplitude Operator) are compared with the in-site monitoring motions. The results of comparisons show the feasibility of the present monitoring system in safety assessments of FPSO and SYMs. Highlights: According to the requirements for production and management, a fully coupled prototype monitoring system of FPSO and SYMs is designed. The global monitoring system is composed of oceanographic monitoring system, vessel motions monitoring system, restoring force of SYMs monitoring system. The verifications of mooring restore force and vessel motion responses of FPSO show the feasibility of the present monitoring system in safety assessments of FPSO and SYMs.